Newborns’ Cranial Vault: Clinical Anatomy and Authors’ Perspective - A. Hegazy, Abdelmonem; A. Hegazy, Mohammad (International Journal of Human Anatomy, 2018)
Cranial vault is the case surrounding the brain. Its structure differs in newborns than in adults in some aspects. Such differences should be clear for both health and family members. Moreover, the anatomy and embryology of fetal skull take a little attention in the previous literature and textbooks. Therefore, this short review aimed to clarify some aspects of anatomy and clinical importance of cranial vault features in newborns. The newborn vault is formed of multiple separate flat bones connected by fibrous tissues with wide soft gaps called fontanelles. Development of bones of skull vault is closely correlated with the expanding growth of the underlying brain. Such brain shouldn't be struggled by continuous tightening of the newborns' vault. Also, the newborn skull could be affected even by a fixed sleeping position.
Keywords: Newborns; Skull cap; Brain development; Anatomy; Tight bandage.